Cardiac Cx43 Signaling Is Enhanced and TGF-β1/SMAD2/3 Suppressed in Response to Cold Acclimation and Modulated by Thyroid Status in Hairless SHRM - Andelova, Katarina; Szeiffova Bacova, Barbara; Sykora, Matus; Pavelka, Stanislav; Rauchova, Hana; Tribulova, Narcis (Biomedicines, 2022)
The hearts of spontaneously hypertensive rats (SHR) are prone to malignant arrhythmias, mainly due to disorders of electrical coupling protein Cx43 and the extracellular matrix. Cold acclimation may induce cardio-protection, but the underlying mechanisms remain to be elucidated. We aimed to explore whether the adaptation of 9-month-old hairless SHRM to cold impacts the fundamental cardiac pro-arrhythmia factors, as well as the response to the thyroid status. There were no significant differences in the registered biometric, redox and blood lipids parameters between hairless (SHRM) and wild type SHR. Prominent findings revealed that myocardial Cx43 and its variant phosphorylated at serine 368 were increased, while an abnormal cardiomyocyte Cx43 distribution was attenuated in hairless SHRM vs. wild type SHR males and females. Moreover, the level of β-catenin, ensuring mechanoelectrical coupling, was increased as well, while extracellular matrix collagen-1 and hydroxyproline were lower and the TGF-β1 and SMAD2/3 pathway was suppressed in hairless SHRM males compared to the wild type strain. Of interest, the extracellular matrix remodeling was less pronounced in females of both hypertensive strains. There were no apparent differences in response to the hypothyroid or hyperthyroid status between SHR strains concerning the examined markers. Our findings imply that hairless SHRM benefit from cold acclimation due to the attenuation of the hypertension-induced adverse downregulation of Cx43 and upregulation of extracellular matrix proteins.
Keywords: hairless SHRM; extracellular matrix; cold acclimation; thyroid hormones; cardiac Cx43